Surface Modification of Macroporous Matrix for Immobilization of Lipase for Fructose Oleic Ester Synthesis - Hani Hilmanto; Chusnul Hidayat; Pudji Hastuti (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
The objective of this research was to modify the matrix surfaces to obtain both hydrophobic matrix (HM) and hydrophilic-hydrophobic matrix (HHM) for enzymatic synthesis of fructose oleic ester (FOE). The modification was performed by the attachment of 2-phenylpropionaldehyde (PPA) and PPA followed by polyethyleneimine (PEI) for HM and HHM, respectively. The results from FT-IR analysis showed that the peak of stretching vibration of NH2 bond decreased and it was followed by an increase of the peak vibration of –C=N– bond at wave number 1667 cm-1. The peak of bending vibrations of the C=C bond also increased. It indicated that PPA was successfully attached on matrix. For HHM, an increase in the peak area of NH2 bond indicated that PEI was also successfully attached on the matrix. The optimum conditions of lipase adsorption were obtained at buffer pH 7 containing 0.5 M NaCl (9.27 mg protein/g matrix) and without NaCl (9.23 mg protein/g matrix) for HM and HHM, respectively. For FOE synthesis, the best immobilized lipase concentration was about 8% and 6% for HM and HHM, respectively. The optimum time of esterification was 24 h and 18 h for HM and HHM, respectively, in which the yields were 75.96% and 85.29%, respectively. The immobilized lipase could be used up to 3 cycles of esterification reaction.